You are on page 1of 3

# Differentiation Techniques Summary

Function
ax n ax n + bx m

Derivative
nax n 1 nax n 1 + bmx m1

(ax + b) n

an(ax + b) n 1
n[ f ( x)]

[ f ( x)]n
sin[ f ( x)] cos[ f ( x)] tan[ f ( x)] cos ec[ f ( x)] sec[ f ( x)] cot[ f ( x)]
sin 1 [ f ( x)]

n1

[ f ' ( x )]

## [ f ' ( x)]cos[ f ( x)]

[ f ' ( x)]sin[ f ( x)]

## [ f ' ( x)]sec 2 [ f ( x)]

[ f ' ( x)]cos ec[ f ( x)]cot[ f ( x)]

## [ f ' ( x)]sec[ f ( x)] tan[ f ( x)]

[ f ' ( x)]cos ec 2 [ f ( x)]

[ f ' ( x)] 2 1 [ f ( x )]

cos 1 [ f ( x)]

[ f ' ( x )] 2 1 [ f ( x )]

tan 1 [ f ( x)]

[ f ' ( x )] 2 1 + [ f ( x )]

Function

Derivative

a f ( x)

a f ( x ) (ln a) f ' ( x)

e f ( x)
ln f ( x)

f ' ( x )e f ( x ) f ' ( x) f ( x)

Product Rule:

Quotient Rule: v du dv u dx dx 2 v

d dv du (uv) = u + v dx dx dx

d u = dx v

## Knowledge of proving specific differential identities: 1. Show that

d 1 (tan 1 x) = dx 1+ x2 Let y = tan 1 x , then tan y = x

## Differentiating both sides wrt x gives sec 2 y

dy dy 1 =1 = dx dx sec 2 y

dy 1 1 = = 2 dx 1 + tan y 1 + x 2

(Similar approaches shall be taken for proving the derivatives of sin 1 x and cos 1 x)

2. Show that

## d x (a ) = (ln a )(a x ) dx x Let y = a , then ln y = x ln a

1 dy dy Differentiating both sides wrt x gives = ln a = y (ln a) y dx dx dy = (a x )(ln a ) (shown) dx ote that many other variations can surface within the examinations, where techniques like implicit differentiation, product rule or quotient rule may have to be employed. Manipulation of derivatives to achieve targeted differential equations: Example: If y = e x ln x, (a) Find
dy . dx

## (b) Show that x SOLUTIO S :

dy 1 1 = e x + e x ln x = e x + y dx x x

d 2 y dy + (1 + x) y = 2e x 2 dx dx

## d2y 1 1 dy = ex ex 2 + 2 dx x x dx x d2y dy 1 1 = ex ex + x = e x e x + e x + xy 2 dx dx x x d2y 1 x 2 + e x xy = 2e x dx x

x d 2 y dy + y xy = 2e x 2 dx dx d 2 y dy + (1 + x) y = 2e x (shown) 2 dx dx